2019
DOI: 10.1103/physrevlett.122.236401
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Topological Superconductors with Mixed Pairing

Abstract: We show that a two-dimensional semiconductor with Rashba spin-orbit coupling could be driven into the second-order topological superconducting phase when a mixed-pairing state is introduced. The superconducting order we consider involves only even-parity components and meanwhile breaks time-reversal symmetry. As a result, each corner of a square-shaped Rashba semiconductor would host one single Majorana zero mode in the second-order nontrivial phase. Starting from edge physics, we are able to determine the pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(34 citation statements)
references
References 85 publications
(113 reference statements)
0
33
1
Order By: Relevance
“…SOTSCs with four corner states. Next, we generalize our findings to a different class of SOTSCs and consider a SOTSC hosting a quadruplet of MCSs [39][40][41][42][43][44][45][46][47][48]. The basic ingredient of our construction here is a minimalist version of a 2D TI [3] proximity coupled to an s-wave superconductor with amplitude sc , introduced in Ref.…”
mentioning
confidence: 77%
“…SOTSCs with four corner states. Next, we generalize our findings to a different class of SOTSCs and consider a SOTSC hosting a quadruplet of MCSs [39][40][41][42][43][44][45][46][47][48]. The basic ingredient of our construction here is a minimalist version of a 2D TI [3] proximity coupled to an s-wave superconductor with amplitude sc , introduced in Ref.…”
mentioning
confidence: 77%
“…Very recently, it was shown that the second-order topological superconductor can be induced by the s+id state when brought in proximity to a Rashba spin-orbit coupled semiconductor. 66 Topological superconductors may support Majorana zero modes in vortex cores, the control of which can enable quantum computations. Our results here are a needed step towards understanding properties of vortices in such systems.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these unique topological matter is usually guaranteed by the coexistence of crystal and non-spatial symmetries, and their classifications go beyond the tenfold way of first-order topological insulators and superconductors [ 9 , 10 , 11 , 12 ]. Besides great theoretical efforts in the study of higher-order topological insulators [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], superconductors [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] and semimetals [ 49 , 50 , 51 , 52 , 53 , 54 ], HOTPs have also been observed in solid state materials [ 55 , 56 ,…”
Section: Introductionmentioning
confidence: 99%